Development of a high-throughput screen for soluble epoxide hydrolase inhibition - Wolf, Nicola M. (2006)
Mammalian soluble epoxide hydrolase (sEH) represents a highly promising new target for drug development. Chemical inhibition of this enzyme in animal models was shown to treat hypertension and vascular inflammation as well as related syndromes. Existing sEH inhibitors are relatively potent and specific. However, the low solubility and relatively fast metabolism of described sEH inhibitors make them less than therapeutically efficient, stating the need for novel inhibitor structures. Therefore, a series of α-cyanoester and α-cyanocarbonate epoxides were evaluated as potential human sEH (HsEH) substrates for the high-throughput screen (HTS) of compound libraries. (3-Phenyl-oxiranyl)-acetic acid cyano-(6-methoxy-naphthalen-2-yl)-methyl ester (PHOME), which displayed the highest aqueous stability and solubility, was selected for the development of an HTS assay with long incubation times at room temperature. Concentrations of HsEH and PHOME were optimized to ensure assay sensitivity, reliability, and reproducibility. Assay validation, which employed these optimized concentrations, resulted in good accuracy (60–100%) and high precision (<7% relative standard deviation). In addition, an overall Z′ value of 0.7 proved the system’s robustness and potential for HTS. The developed assay system will be a valuable tool to discover new structures for the therapeutic inhibition of sEH to treat various cardiovascular diseases.